PENILAIAN POTENSI BANJIR BANDANG MENGGUNAKAN METODE FLASH FLOOD POTENTIAL INDEX (FFPI) DENGAN MODEL KRUZDLO (STUDI KASUS: SUB DAS WAY ILAHAN, LAMPUNG) - Fitriana, Indri Rahmandhani; Sahid, Sahid; Putra, Riyan Hari (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
A flash flood is a rapidly occurring flood with a high discharge rate and significant destructive power. Flash floods result from a combination of natural factors and human activities and have serious consequences for society, such as loss of life, infrastructure damage, and environmental impact. This study aims to map the potential hazard areas of flash floods in the catchment area of Way Ilahan, Tanggamus Regency, Lampung Province using the Flash Flood Potential Index (FFPI) method based on GIS with the Kruzdlo model (2010). This method processes spatial data such as slope maps, vegetation density, land use, and soil texture. Through this approach, flash flood hazard classes can be identified based on regional characteristics analyzed within a GIS system using raster processing techniques. The study results indicate that 363.63 hectares of the Way Ilahan catchment area fall into the high-category flash flood hazard class, while 19,089.18 hectares are categorized under the medium-level hazard class. Through this mapping, relevant stakeholders such as local governments and communities can take more effective preventive measures to reduce the impact of flash flood disasters.